Intravitreal live gnathostoma spinigerum - Basak Samar; Sinha Tushar; Bhattacharya Debasish; Hazra Tushar; Parikh Sunil (Indian Journal of Ophthalmology, 2004)
Intraocular infestation by live Gnathostoma spinigerum is a rare occurrence in humans. Most of the published reports are from South-East Asia. We report a case of intravitreal gnathostomiasis, where the worm was removed live and intact by pars plana vitrectomy.